Mary Ellen Bute : Pioneer Animator - Basquin, Kit Smyth (Book collections on Project MUSE., 2020)
"Mary Ellen Bute: Pioneer Animator captures the personal and professional life of Mary Ellen Bute (1906-1983) one of the first American filmmakers to create abstract animated films in 1934, also one of the first Americans to use the electronic image of the oscilloscope in films starting in 1949, and the first filmmaker to interpret James Joyce's literature for the screen, Passages from James Joyce's Finnegans Wake, a live-action film for which she won a Cannes Film Festival Prize in 1965." -- Amazon.com.